Efeitos do exercício físico em modelo experimental de lesão medular - Barros, Natalie de Almeida (2022)
Introduction: Resistance training has added to be a promising alternative in improving quality of life and functional independence in compliance with spinal cord injury. Objective: To analyze physical exercise in an experimental model of spinal cord injury. Methodology: The study was carried out in two stages. Step 1: systematic review to synthesize scientific evidence on exercise as a treatment strategy in an experimental model of spinal cord injury. A systematic search of articles published until December 2021 was performed in six databases, using the terms “spinal injury” and “exercise therapy”. Study selection and data extraction were performed by two independent reviewers. The risk of bias assessment was performed using the SYRCLE Animal Studies Bias Risk Tool. Step 2: evaluation of resistance training response in muscle damage and oxidative stress markers in an experimental model of spinal cord injury. Forty Wistar rats were used, distributed equally into five groups (n = 8 per group): animals that did not undergo any intervention (C); animals that were diagnosed during the surgical procedure but did not suffer spinal cord injury (S); animals that were damaged to spinal cord injury and did not train (SD); animals that were damaged to spinal cord injury and underwent training (L); trained animals that were injured in spinal cord injury and retrained (TL). For the surgical procedure, the animals were anesthetized and had a spinal cord injury at the level of the thoracic vertebra. The animals in the training groups (L and TL) were collected in a resistance training protocol in an adapted vertical ladder model, with a frequency of three times a week for four weeks. At the end of the protocol, the animals were euthanized and the biological material collected for analysis of muscle damage and oxidative stress. Results: In the systematic review, 78 articles were included, of which 60 used rats and of these, 49 were female. The region of predilection for induction of spinal cord injury was the thoracic and the most used method of locomotor assessment was the Basso, Beattie and Bresnahan scale. As for the risk of bias, the “high” or “uncertain” risk was found in all evaluated domains. In the experimental study, it was found that the animals submitted to resistance training showed significant differences (considered p<0.05) in muscle damage and oxidative stress markers, evidencing here, the group that was previously trained before being submitted to the injury (TL ). While the sedentary group (SD) had higher levels of oxidative stress, LDH and AST. Conclusion: Although resistance training is a promising therapeutic strategy, there are still scientific gaps to be filled in order to provide information for the creation of guiding protocols for the treatment of spinal cord injury.